Influential Factors Contributing to Stroke Recovery: A Review - Tun, Su Sandi Hla; Wanpen, Sawitri; Nualnetr, Nomjit (Universitas Muhammadiyah Surakarta, 2023)
Stroke is a major public health problem affecting disability to people after stroke. Deficits in motor function resulting from stroke can impact the mobility of patient, ability to perform tasks in everyday life, social interaction, and likelihood of resuming work. The recovery of stroke is important for the survivors to return to daily life. Several factors influence the stroke recovery and can predict the conditions of the patients to obtain the optimal rehabilitative therapeutics individually. The aim of the paper is to evaluate the influential factors contributing to stroke recovery. When the clinicians from rehabilitation teams have a better understanding of these individualized factors, the therapeutic goals can become holistic, effective and realistic for the patients to achieve the maximal motor function recovery after stroke.